Gender Integration in Islamic Politics: Fiqh Siyasah on Women's Political Rights since Classical to Contemporary Interpretations - Sulastri Caniago; Firdaus; Zainal Azwar; Dian Pertiwi; Dasrizal Marah Nainin (Faculty of Sharia, IAIN Metro, 2024)
This study examines the controversy surrounding gender equality in women's political rights in the public sphere. This discussion arises from differing interpretations of existing texts, which have persisted from the classical era to the contemporary period. This study employs normative legal research, utilizing library materials and secondary data as primary sources. It involves reviewing literature, including articles, books, and other relevant resources. The collected data, comprising primary and secondary legal materials, is analyzed qualitatively and presented descriptively. The study finds that Islam upholds gender equality by placing women in a noble and honorable position and affirming their rights and roles as stated in the words of Allah. Among classical Islamic scholars, there is debate about whether women are permitted to hold leadership roles. Imam Malik, Imam Shafi'i, and Ahmad Ibn Hanbal prohibited it, while Imam Abu Hanifah allowed women to lead if they possessed adequate capability and competence. Scholars like Ibn Jarir Al-Tabari and Ibn Hazm also allowed women to assume leadership positions without any conditions. Contemporary scholars, including Ibn Ashur, Yusuf al-Qaradawi, and Quraish Shihab, support women's participation in politics, both in voting and being elected. Yusuf al-Qaradawi, however, set conditions, emphasizing that women must adhere to Islamic ethics, fulfill their duties as wives and mothers, and not violate Sharia principles. If the exercise of women's political rights leads to harm, it is prohibited based on the principle of sadd al-zari'ah. This study contributes to the understanding of Islamic perspectives on gender equality in politics, examining viewpoints from both classical and contemporary scholars. It also provides a discourse on the conditions required for women to exercise their political rights within the framework of Islamic law.